The Protocatechuate 3,4-Dioxygenase Solubility (PCDS) Tag Enhances the Expression and Solubility of Heterogenous Proteins in Escherichia coli - Zou, Lei; Li, Sha; Li, Nan; Ruan, Shi-Long; Chen, Jing; Wu, Jing; Yan, Dazhong; Chao, Hong-Jun (Frontiers in Microbiology, 2021)
Escherichia coli has been developed as the most common host for recombinant protein expression. Unfortunately, there are still some proteins that are resistant to high levels of heterologous soluble expression in E. coli. Protein and peptide fusion tags are one of the most important methods for increasing target protein expression and seem to influence expression efficiency and solubility as well. In this study, we identify a short 15-residue enhancing solubility peptide, the PCDS tag, which enhances heterologous protein expression in E. coli. This PCDS tag is a 45-bp long sequence encoding a peptide tag involved in the soluble expression of protocatechuate 3, 4-dioxygenase, encoded by the pcaHG genes of Pseudomonas putida NCIMB 9866. This tag was shown to be necessary for the heterologous soluble expression of PcaHG98 in E. coli. Purified His6-PcaHG98e04-PCDS exhibited an activity of 205.6 U/mg against protocatechuate as a substrate, and this activity was not affected by a PCDS tag. The total protein expressions of YFP-PCDS and YFPt-PCDS were significantly amplified up to 1.6-fold and 2-fold, respectively, compared to YFP alone. Accordingly, His6-YFP-PCDS and His6-YFPt-PCDS had 1.6-fold and 3-fold higher soluble protein yields, respectively, than His6-YFP expressed under the same conditions. His6-YFP, His6-YFP-PCDS, and His6-YFPt-PCDS also showed consistent fluorescence emission spectra, with a peak at 530 nm over a scanning range from 400 to 700 nm. These results indicated that the use of the PCDS tag is an effective way to improve heterologous protein expression in E. coli.